Comparison Of Viscosity Among Four Orthodontic Adhesive Primers In Two Different Temperatures - Azrul Hafiz Abdul Aziz (Shiraz University of Medical Sciences, Iran, 2024)
Statement of Problem: The viscosity of orthodontics adhesive primers is crucial for stability and correct brackets ‘position during bond up. An excessive adhesive flow during brackets seating could change the brackets’ position.Objectives: The main purpose of this study was to investigate the viscosity of four orthodontic adhesive primers in two different temperatures.Materials and Methods: Four orthodontic adhesive primers were used in this study. They include Transbond self-etching primer (SEP; 3M Unitek, USA), Transbond XT (3M Unitek, USA), Transbond moisture insensitive primer (MIP; 3M Unitek, USA), and Unite adhesive primer (3M Unitek, USA). A controlled stress rheometer (Carri-Med MKII, UK) with truncated cone and plate were used to investigate the viscosity of each orthodontic adhesive primer in two different temperatures. The orthodontic adhesive primers were tested at 25oC and 35oC for five times to calculate the means for each material during ascent and descent of the controlled stress rheometer. Statistical analysis was done with one-way ANOVA and two-sample t-test.Results: In this study, a statistically significant difference was found among viscosity of different orthodontic adhesive primers (p=0.005). At 25oC, the Transbond XT (192.20±1.21 MPa?s) was the most viscous primer and Transbond MIP (21.74±1.50 MPa?s) the least viscous one. Unite adhesive primer (143.40±2.17 MPa?s) was the second most viscous primer followed by Transbond SEP (44.28±3.09 MPa?s). The difference of the viscosity of orthodontic adhesive primers was also statistically significant when compared in two different temperatures.Conclusions: This study showed that there was a statistically significant difference among the viscosity of the four orthodontic adhesive primers. Moreover, the viscosity of orthodontic adhesive primers also changed with temperatures. This might affect the orthodontic bond up procedure during summer and winter.